TEKNIK TONGUING DAN VIBRATO SAXOPHONE ALTO PADA LAGU BE. NO 720 NAENG MARSINONDANG NGOLUNGKU DI GEREJA HKBP LUMBAN SIAGIAN - Bobby Lumban Tobing; Robert KA. Simangunsong; Boho Parulian Pardede; Roy JM. Hutagalung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe and analyze the application of playing techniques, specifically tonguing and vibrato, on the alto saxophone in performing the song Buku Ende (BE) No. 720 "Naeng Marsinondang Ngoluku" at the HKBP Lumban Siagian Church. The main focus of this research is how these techniques are utilized to strengthen the musical expression and spiritual message contained within the song. The research method employed is qualitative with a descriptive approach. Data were collected through field observations, in-depth interviews with the musician (saxophone player), and documentation in the form of audio recordings and musical score studies. The results of the study indicate that: (1) The dominant tonguing technique used is soft tonguing to produce clear yet smooth articulation, aligning with the solemn character of the song. (2) The vibrato technique is applied selectively on long notes to provide emotional emphasis and more vibrant dynamics. (3) The combination of these two techniques at HKBP Lumban Siagian Church is proven effective in supporting a solemn worship atmosphere and assisting the congregation in internalizing the meaning of the song more deeply.